2015
DOI: 10.1088/1748-9326/10/12/125011
|View full text |Cite
|
Sign up to set email alerts
|

Which came first, people or pollution? A review of theory and evidence from longitudinal environmental justice studies

Abstract: A considerable number of quantitative analyses have been conducted in the past several decades that demonstrate the existence of racial and socioeconomic disparities in the distribution of a wide variety of environmental hazards. The vast majority of these have been cross-sectional, snapshot studies employing data on hazardous facilities and population characteristics at only one point in time. Although some limited hypotheses can be tested with cross-sectional data, fully understanding how present-day dispari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
143
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(144 citation statements)
references
References 41 publications
1
143
0
Order By: Relevance
“…A substantial body of literature documents that polluting facilities are more likely to be located in areas with a higher proportion of minority residents (Mohai et al, 2009). A recent analysis on siting of commercial hazardous waste facilities in 1991-1995 found that higher percentages of Asian residents, not those of black and Hispanic residents, in the surrounding area were strongly associated with higher likelihood of siting of such facilities, with or without adjustment for socioeconomic characteristics of the surrounding area (Mohai and Saha, 2015). This finding indicates that the observed tendency for non-Hispanic Asians to have the highest blood cadmium among never and former smokers of three racial minority groups could be potentially explained in part by the unequal burden of living near polluting facilities borne by Asians.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of literature documents that polluting facilities are more likely to be located in areas with a higher proportion of minority residents (Mohai et al, 2009). A recent analysis on siting of commercial hazardous waste facilities in 1991-1995 found that higher percentages of Asian residents, not those of black and Hispanic residents, in the surrounding area were strongly associated with higher likelihood of siting of such facilities, with or without adjustment for socioeconomic characteristics of the surrounding area (Mohai and Saha, 2015). This finding indicates that the observed tendency for non-Hispanic Asians to have the highest blood cadmium among never and former smokers of three racial minority groups could be potentially explained in part by the unequal burden of living near polluting facilities borne by Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the United States, lower income populations are more likely to live near industrial facilities such as coal-fired power plants (Collins et al, 2016;Mohai et al, 2009;Mohai & Saha, 2015;Schulz et al, 2016). Exposure to environmental pollutants generated by these industrial sources, including ambient air pollution, is inequitably distributed by class and race (Ash et al, 2013;Brown, 1995;Pastor et al, 2005;Zwickl et al, 2014) and may contribute to differences in health outcomes (Adler & Newman, 2002;Apelberg et al, 2005;Collins et al, 2011;Morello-Frosch & Jesdale, 2006;Rice et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This study uses cross-sectional data, meaning it provides a statistical "snapshot" of associations rather than examining causality or correlations over time. Quantitative environmental inequality work has largely consisted of cross-sectional work, due to difficulty in obtaining longitudinal data on both hazardous facilities and neighborhood-level social dynamics (Mohai and Saha 2015). 6…”
Section: Methodsmentioning
confidence: 99%
“…This review focuses on empirical studies of “disparate proximity,” which quantitatively assess whether “members of a specific social group live closer to some set of hazards than we would expect if group members were randomly distributed across residential space” (Downey :355). Disparate proximity studies often analyze the extent to which race or class characterizes communities near hazards in urban areas (for reviews see Brulle and Pellow ; Mohai, Pellow, and Roberts ; Mohai and Saha ; Pellow and Brehm 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation